Controlled K-Fusion Frame for Hilbert Spaces - Assila Nadia; Kabbaj Samir; Moalige Brahim (Moroccan Journal of Pure and Applied Analysis, 2021)
K-fusion frames are a generalization of fusion frames in frame theory. In this paper, we extend the concept of controlled fusion frames to controlled K-fusion frames, and we develop some results on the controlled K-fusion frames for Hilbert spaces, which generalize some well known results of controlled fusion frame case. Also we discuss some characterizations of controlled Bessel K-fusion sequences and of controlled K-fusion frames. Further, we analyze stability conditions of controlled K-fusion frames under perturbation.